2017
DOI: 10.1007/s10461-017-1809-3
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Exploration of the Needs of People Living with HIV (PLWH) Enrolled in Access to Care, a National HIV Linkage, Retention and Re-Engagement in Medical Care Program

Abstract: Competing needs pose barriers to engagement in HIV medical care. Mixed methods were used to explore and describe the needs of participants enrolled in Access to Care, a national HIV linkage, retention and re-engagement in care (LRC) program that served people living with HIV who knew their status but were not engaged in care. When asked to prioritize their most urgent needs, participants reported housing or shelter (31%), HIV medical services (24%), and employment (8%). When we assessed the HIV continuum of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Our results are consistent with numerous other studies which have found that unmet transportation needs have a negative impact on retention in care and clinical outcomes. 24,34,35 The evidence from our study supports broadening and strengthening transportation assistance programs.…”
Section: Discussionsupporting
confidence: 66%
“…Our results are consistent with numerous other studies which have found that unmet transportation needs have a negative impact on retention in care and clinical outcomes. 24,34,35 The evidence from our study supports broadening and strengthening transportation assistance programs.…”
Section: Discussionsupporting
confidence: 66%
“…In the Southern US, medical mistrust [ 4 ] and pervasive stigmas (e.g., around HIV [ 5 ], minority sexual orientation, poverty, substance abuse, and mental disorders [ 6 ]) pose additional retention challenges [ 7 ]. Evidence-based retention interventions address many of these barriers and include: provision of social support services, case management [ 8 ], child care, housing services, appointment reminders, co-location of services, appointment accompaniment [ 9 ], patient navigators [ 10 ], peer support [ 11 ], educational brochures [ 12 ], outreach, and transportation assistance [ 8 , 9 , 13 16 ]. While each of these interventions has demonstrated promise, continued shortcomings in achieving national retention goals suggest the need for new re-engagement and retention strategies tailored to the needs of PLWH who have fallen out of care [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…No measure of substance use was associated with retention in care which is not consistent with other studies. 39 This may be due to the lack of validated measures of substance use that are used by the Ryan White Program system given their primary goal of identifying client service needs.…”
Section: Discussionmentioning
confidence: 99%